Effects of Ischemic Preconditioning and Postconditioning in a Renal Ischemia-Reperfusion Injury Model: A Comparative Experimental Study in Rats - Arantes, V. M. [UNESP]; Bueno, R. T. [UNESP]; Modolo, R. P.; Domingues, M. A. C. [UNESP]; Carvalho, L. R. de [UNESP]; Nascimento Junior, P. do [UNESP]; Modolo, N. S. P. [UNESP] (Elsevier B.V., 2018)
Background. Ischemia-reperfusion injury is an unavoidable aspect of transplantation, as well as an important cause of acute kidney injury in clinical practice. Pre- and post-ischemic conditioning are strategies that may provide organs with resistance to major ischemic events. This study evaluates the effects of ischemic preconditioning and ischemic postconditioning, either separately or in combination, after an acute ischemia-reperfusion kidney injury. Methods. Forty Wistar rats received isoflurane anesthesia and were randomized into 5 groups: 1. the sham group underwent laparotomy; 2. the control group underwent laparotomy and 30 minutes of renal ischemia followed by reperfusion; 3. the preconditioning group underwent laparotomy, ischemic preconditioning, and 30 minutes of renal ischemia followed by reperfusion; 4. the preconditioning and postconditioning group underwent laparotomy, ischemic preconditioning, 30 minutes of renal ischemia, and ischemic postconditioning followed by reperfusion; and 5. the postconditioning group underwent laparotomy, 30 minutes of renal ischemia, and ischemic postconditioning followed by reperfusion. Serum analyses of creatinine and neutrophil gelatinase-associated lipocalin (NGAL) were performed, and renal histology was examined 24 hours later. Results. Severe tubular injury and increases in creatinine were observed in all groups except the sham group. The control group and all ischemic conditioning groups were no different in the degree of renal injury and values of NGAL and creatinine after the injury. Conclusions. Ischemic preconditioning and ischemic postconditioning, together or separately, are unable to preserve kidney function or exert a protective effect against tubular cell injury after an acute ischemia-reperfusion kidney injury.